Evaluasi Beban Kerja Pekerja Divisi Quality Control PT. X dengan Metode Work Sampling - Taruna, Malvin; -, Yanto (Metris: Jurnal Sains dan Teknologi, 2021)
This study aimed to determine the workload of the workers to be used for incentive plan in the Quality Control Division, Company X. Studying work characteristics, a work sampling technique was used. Two workers from this QC division were participated in the study. A number of 440 observation were taken from each Worker 1 and Worker 2. Results showed that the percentages of productive time are 93.62% for Worker 1 and 91.81% for Worker 2. Meanwhile for workload resulted 151% and 138% for Worker 1 and Worker 2 (classified as overload for both workers). This study recommended the company to add one more worker to help in this workstation to reduce the workload of these two workers